Inhibition of lncRNA NFIA-AS1 Alleviates Abnormal Proliferation and Inflammation of Vascular Smooth Muscle Cells in Atherosclerosis by Regulating miR-125a-3p/AKT1 Axis - Yi Zhu; Xiaofeng Tian; Yan Wang; Chengxiang Wang; Naiquan Yang; Lianghong Ying; Hongyan Niu (International Journal of Genomics)
Vascular smooth muscle cells (VSMCs) are critical elements of the vascular wall and play a crucial role in the genesis and development of atherosclerosis (AS). Increasingly, studies have indicated that long noncoding RNAs (lncRNAs) regulate VSMC proliferation, apoptosis, and other biological processes. Nevertheless, the role of lncRNA NFIA-AS1 (hereinafter referred to as NFIA-AS1) in VSMCs and AS remains unclear. Quantitative real-time PCR (qRT-PCR) was performed to analyze the messenger RNA (mRNA) levels of NFIA-AS1 and miR-125a-3p. CCK-8 and EdU staining were performed to detect VSMC proliferation. VSMC apoptosis was evaluated by flow cytometry. The expression of various proteins was detected using western blotting. The levels of inflammatory cytokines secreted by VSMCs were measured by enzyme linked immunosorbent assay (ELISA). The binding sites of NFIA-AS1 and miR-125a-3p, as well as miR-125a-3p and AKT1, were analyzed using bioinformatics methods and validated using a luciferase reporter assay. The function of NFIA-AS1/miR-125a-3p/AKT1 in VSMCs was clarified through loss- and gain-of-functional experiments. We confirmed that NFIA-AS1 was highly expressed in AS tissues and VSMCs induced by oxidized low-density lipoprotein (Ox-LDL). Knockdown of NFIA-AS1 restrained the exceptional growth of Ox-LDL-induced VSMCs, promoted their apoptosis, and decreased the secretion of inflammatory factors and expression of adhesion factors. In addition, NFIA-AS1 regulated the proliferation, apoptosis, and inflammatory response of VSMCs through the miR-125a-3p/AKT1 axis, suggesting that NFIA-AS1 may be a potential therapeutic target for AS.